Modified sutureless and glue-free method versus conventional sutures for conjunctival autograft fixation in primary pterygium surgery: a systematic review and meta-analysis - Faisal Aljahdali; Waleed Khayyat; Abdulelah T BinYamin; Sultan A Al-Qahtani; Mohammed D Alghamdi; Ali Saleh Alsudais; Husain A Alalgum; Halah Bin Helayel; Mohammed AlMutlak (BMJ Open Ophthalmology)
Background Pterygium is a common ocular surface disorder that requires surgical intervention for treatment. Conjunctival autografts are preferred over simple excision due to lower recurrence rates. This systematic review and meta-analysis compared the modified sutureless glue-free (MSGF) method with conventional sutures (CS) for conjunctival autograft fixation in primary pterygium surgery.Methods A comprehensive search was conducted in MEDLINE, Embase, CENTRAL, Google Scholar and ClinicalTrials.gov for randomised controlled trials (RCTs) comparing MSGF and CS conjunctival autografts. Outcome measures included operation time, recurrence and postoperative complications. Standardised mean difference (SMD) and risk ratio (RR) were used for continuous and dichotomous outcomes, respectively.Results 11 RCTs involving 833 participants were included. The analysis revealed that MSGF had a significantly shorter operation time compared with CS (SMD −3.704, 95% CI −5.122 to −2.287, p<0.001). CS was associated with a higher risk of foreign body sensation (RR 0.22, 95% CI 0.06 to 0.74, p=0.01). MSGF was associated with a higher risk of graft dehiscence (RR 9.01, 95% CI 2.74 to 29.68, p=0.000) and graft retraction (RR 2.37, 95% CI 1.17 to 4.77, p=0.02). No significant differences were found in recurrence, graft haemorrhage, granuloma, Dellen and conjunctival oedema.Conclusion Using the MSGF technique in conjunctival autograft fixation for pterygium surgery reduces operation time by relying solely on the patient’s blood for fixation. However, it increases the risk of graft dehiscence and retraction. However, CS is linked to a higher likelihood of experiencing foreign body sensations. Understanding the learning curve and surgeon familiarity with novel techniques is crucial for optimising patient care and surgical outcomes, while individualised decision-making is necessary considering the advantages and disadvantages of each approach. Further research is warranted to minimise complications and optimise surgical outcomes.